Masitinib for treatment of severely symptomatic indolent systemic mastocytosis: a randomised, placebo-controlled, phase 3 study. Issue 10069 (11th February 2017) - Lortholary, Olivier; Chandesris, Marie Olivia; Livideanu, Cristina Bulai; Paul, Carle; Guillet, Gérard; Jassem, Ewa; Niedoszytko, Marek; Barete, Stéphane; Verstovsek, Srdan; Grattan, Clive; Damaj, Gandhi; Canioni, Danielle; et al.
Summary: Background: Indolent systemic mastocytosis, including the subvariant of smouldering systemic mastocytosis, is a lifelong condition associated with reduced quality of life. Masitinib inhibits KIT and LYN kinases that are involved in indolent systemic mastocytosis pathogenesis. We aimed to assess safety and efficacy of masitinib versus placebo in severely symptomatic patients who were unresponsive to optimal symptomatic treatments. Methods: In this randomised, double-blind, placebo-controlled, phase 3 study, we enrolled adults (aged 18–75 years) with indolent or smouldering systemic mastocytosis, according to WHO classification or documented mastocytosis based on histological criteria, at 50 centres in 15 countries. We excluded patients with cutaneous or non-severe systemic mastocytosis after a protocol amendment. Patients were centrally randomised (1:1) to receive either oral masitinib (6 mg/kg per day over 24 weeks with possible extension) or matched placebo with minimisation according to severe symptoms. The primary endpoint was cumulative response (≥75% improvement from baseline within weeks 8–24) in at least one severe baseline symptom from the following: pruritus score of 9 or more, eight or more flushes per week, Hamilton Rating Scale for Depression of 19 or more, or Fatigue Impact Scale of 75 or more. We assessed treatment effect using repeated measures methodology for rare diseases via the generalised estimating equation model in a modified intention-to-treat population, including all participants assigned to treatment minus those who withdrew due to a non-treatment-related cause. We assessed safety in all patients who received at least one dose of study drug. This trial is registered withClinicalTrials.gov, numberNCT00814073 . Findings: Between Feb 19, 2009, and July 15, 2015, 135 patients were randomly assigned to masitinib (n=71) or placebo (n=64). By 24 weeks, masitinib was associated with a cumulative response of 18·7% in the primary endpoint (122·6 responses of 656·5 possible responses [weighted generalised estimating equation]) compared with 7·4% for placebo (48·9 of 656·5; difference 11·3%; odds ratio 3·6; 95% CI 1·2–10·8; p=0·0076). Frequent severe adverse events (>4% difference from placebo) were diarrhoea (eight [11%] of 70 in the masitinib group vs one [2%] of 63 in the placebo group), rash (four [6%] vs none), and asthenia (four [6%] vs one [2%]). The most frequent serious adverse events were diarrhoea (three patients [4%] vs one [2%]) and urticaria (two [3%] vs none), and no life-threatening toxicities occurred. One patient in the placebo group died (unrelated to study treatment). Interpretation: These study findings indicate that masitinib is an effective and well tolerated agent for the treatment of severely symptomatic indolent or smouldering systemic mastocytosis. Funding: AB Science (Paris, France).